Stealing from the Heart: A Rare Case of Chest Pain Post-Coronary Artery Bypass Grafting - Prasanti A. Kotta; Joshua R. Hirsch; Umair Khalid; Ali E. Denktas (Methodist DeBakey Cardiovascular Journal)
A 70-year-old veteran with prior triple vessel coronary artery bypass grafting (CABG) presented with exertional chest pain. His work-up revealed > 40 mm Hg bilateral upper extremity blood pressure difference. Chest computed tomography and invasive angiography revealed severe stenosis at the ostium of the left subclavian artery, proximal to the origin of the left internal mammary artery to left anterior descending artery graft (LIMA-LAD). A diagnosis of coronary subclavian steal syndrome (CSSS) was made, and carotid-subclavian bypass was performed. This case outlines when to suspect CSSS, an approach to its diagnosis, and the importance of its timely management.